Unusual N-Prenylation in Diazepinomicin Biosynthesis: The Farnesylation of a Benzodiazepine Substrate Is Catalyzed by a New Member of the ABBA Prenyltransferase Superfamily - Bonitz, Tobias; Zubeil, Florian; Grond, Stephanie; Heide, Lutz (PLOS ONE, 2013)
The bacterium Micromonospora sp. RV115, isolated from a marine sponge, produces the unusual metabolite diazepinomicin, a prenylated benzodiazepine derivative. We have cloned the prenyltransferase gene dzmP from this organism, expressed it in Escherichia coli, and the resulting His8-tagged protein was purified and investigated biochemically. It was found to catalyze the farnesylation of the amide nitrogen of dibenzodiazepinone. DzmP belongs to the ABBA prenyltransferases and is the first member of this superfamily which utilizes farnesyl diphosphate as genuine substrate. All previously discovered members utilize either dimethylallyl diphosphate (C5) or geranyl diphosphate (C10). Another putative diazepinomicin biosynthetic gene cluster was identified in the genome of Streptomyces griseoflavus Tü4000, suggesting that the formation of diazepinomicin is not restricted to the genus Micromonospora. The gene cluster contains a gene ssrg_00986 with 61.4% identity (amino acid level) to dzmP. The gene was expressed in E. coli, and the purified protein showed similar catalytic properties as DzmP. Both enzymes also accepted other phenolic or phenazine substrates. ABBA prenyltransferases are useful tools for chemoenzymatic synthesis, due to their nature as soluble, stable biocatalysts. The discovery of DzmP and Ssrg_00986 extends the isoprenoid substrate range of this superfamily. The observed prenylation of an amide nitrogen is an unusual biochemical reaction.